Procedural Justice, Legitimacy, and Public Cooperation with Police: Does Western Wisdom Hold in China?. (July 2017) - Sun, Ivan Y.; Wu, Yuning; Hu, Rong; Farmer, Ashley K.
Objectives: The principal objective of the current study is to test the applicability of Tom Tyler's process-based model of policing in China. A secondary objective of this research is to examine the internal consistency and discriminant validity of key composite constructs in Tyler's model. Methods: Using survey data collected from approximately 1, 000 residents in a Chinese city, ordinary least squares regression was employed to assess the direct and indirect (through legitimacy) effects of procedural justice, specific distributive justice, and police effectiveness on willingness to cooperate with the police. Results: The internal consistency and discriminant validity of key composites in Tyler's original model appear questionable with the Chinese data. Procedural justice, just like in the West, plays a significant role in predicting Chinese views on police legitimacy and willingness to cooperate with the police. Meanwhile, the strongest predictor of Chinese perceptions of police legitimacy is police effectiveness. The impact of both distributive justice and effectiveness on Chinese willingness to cooperate is mainly indirect through police legitimacy. Conclusions: Key arguments of Tyler's model are largely supported by the Chinese data. Future research needs to develop culture-specific measures to further elaborate Tyler's process-based model of policing.